Oral microbiome and risk of malignant esophageal lesions in a high-risk area of China: A nested case-control study - Liu, Fangfang (Chin J Cancer Res, 2020)
OBJECTIVE: We aimed to prospectively evaluate the association of oral microbiome with malignant esophageal lesions and its predictive potential as a biomarker of risk. METHODS: We conducted a case-control study nested within a population-based cohort with up to 8 visits of oral swab collection for each subject over an 11-year period in a high-risk area for esophageal cancer in China. The oral microbiome was evaluated with 16S ribosomal RNA (rRNA) gene sequencing in 428 pre-diagnostic oral specimens from 84 cases with esophageal lesions of severe squamous dysplasia and above (SDA) and 168 matched healthy controls. DESeq analysis was performed to identify taxa of differential abundance. Differential oral species together with subject characteristics were evaluated for their potential in predicting SDA risk by constructing conditional logistic regression models. RESULTS: A total of 125 taxa including 37 named species showed significantly different abundance between SDA cases and controls (all P<0.05 & false discovery rate-adjusted Q<0.10). A multivariate logistic model including 11 SDA lesion-related species and family history of esophageal cancer provided an area under the receiver operating characteristic curve (AUC) of 0.89 (95% CI, 0.84−0.93). Cross-validation and sensitivity analysis, excluding cases diagnosed within 1 year of collection of the baseline specimen and their matched controls, or restriction to screen-endoscopic-detected or clinically diagnosed case-control triads, or using only bacterial data measured at the baseline, yielded AUCs>0.84. CONCLUSIONS: The oral microbiome may play an etiological and predictive role in esophageal cancer, and it holds promise as a non-invasive early warning biomarker for risk stratification for esophageal cancer screening programs.